Pronunciation proficiency and musical aptitude in Spanish as a foreign language: results of an experimental research project - Lieve Vangehuchten; Veronique Verhoeven; Peter Thys (Revista de Lingüística y Lenguas Aplicadas, 2015)
This paper examines the correlation between musical aptitude and pronunciation proficiency in an experiment with 29 university students of Spanish as a foreign language. The 29 participants took a test in Spanish pronunciation and prosody as well as in musicality. The pronunciation and prosody test consisted of two parts. The first part was a receptive phonemic discrimination test and the second part was a productive test in which they had to repeat words and sentences chosen for their prosodic characteristics. The musical aptitude test also consisted of a receptive part on musicality in general, as well as a productive part, which included the reproduction of tones, tone intervals, rhythms and the singing of a melody. The statistical analysis with Pearson’s correlation-coefficients revealed a positive correlation (although not for all aspects) between the musical and foreign language pronunciation proficiency aptitudes. The results are commented on in the discussion. Relevant teaching implications are included in the conclusion.